Synergism of nitrogen uptake from soil and symbiotic nitrogen fixation increasing nitrogen in soybean plant ( Glycine max) - Rushel, Alaídes Puppin; Ruschel, Renato (Pesquisa Agropecuaria Brasileira, 2014)
The effect of inoculation and different sources of nitrogen (potassium nitrate, ammonium sulphate, ammonium nitrate and urea) on nodulation, i.e., the number and weight of nodules, the symbiotic N-fixation and the amount of N, total and percentual, in the soybean plant (Glycine max (L.) Merril) was studied. Nodular weight decreased with addition of ammonium sulphate, ammonium nitrate and potassium nitrate to soil. This effect was not observed with urea. Although the number of nodules decreased with addition of these nitrogen sources, no inhibition of nitrogenase activity was noted. The plant dry weight measured at 45 days indicated no differences due to inoculation; however, inoculation proved effective as far as increase in total and percentual N in plant tops in all treatments under study. The increase in total nitrogen indicated a synergism of inoculation and nitrogen fertilization. Inoculation maintained a constant level of nitrogen in the plant throughout plant growth.